2015
DOI: 10.1016/j.grj.2014.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and spatial variability in event scale aeolian transport on Ameland, The Netherlands

Abstract: a b s t r a c tCoastal dunes are the primary defence protecting the coastline from the destructive forces of the sea in The Netherlands. Aeolian processes are important in this context as they contribute to dune accretion and thus the safety of the coastal hinterland. In this study, we analyze horizontal and vertical variability of event scale aeolian sand transport on a wide beach on the island of Ameland, The Netherlands. Data were obtained from a meteorological station, groundwater monitoring wells and a ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 83 publications
0
13
0
Order By: Relevance
“…Generally, winds exceeding the sediment entrainment velocity threshold mobilize sand from the sub‐aerial portion of the beach and deposit it when wind speeds are reduced around vegetation and topographic features, typically within the upper backshore and incipient dune (Hesp, ). Transport magnitudes are controlled by wind speed, duration and fetch (Davidson‐Arnott et al ., ; Anthony et al ., ; Delgado‐Fernandez, ; Bauer et al ., ; Keijsers et al ., ), vegetation (Feagin, ; Bitton and Hesp, ; Charbonneau et al ., ), topographic slope breaks (Walker et al ., ), as well as supply‐limiting factors including moisture content (Davidson‐Arnott et al ., , ), beach width, sediment supply and sediment characteristics (Bauer and Davidson‐Arnott, ; Poortinga et al ., ; Crapoulet et al ., ). Dune growth, however, may be interrupted by hydrodynamic processes, especially during stormy periods when elevated water levels and runup may reach and erode the dune (Sallenger, ).…”
Section: Introductionmentioning
confidence: 99%
“…Generally, winds exceeding the sediment entrainment velocity threshold mobilize sand from the sub‐aerial portion of the beach and deposit it when wind speeds are reduced around vegetation and topographic features, typically within the upper backshore and incipient dune (Hesp, ). Transport magnitudes are controlled by wind speed, duration and fetch (Davidson‐Arnott et al ., ; Anthony et al ., ; Delgado‐Fernandez, ; Bauer et al ., ; Keijsers et al ., ), vegetation (Feagin, ; Bitton and Hesp, ; Charbonneau et al ., ), topographic slope breaks (Walker et al ., ), as well as supply‐limiting factors including moisture content (Davidson‐Arnott et al ., , ), beach width, sediment supply and sediment characteristics (Bauer and Davidson‐Arnott, ; Poortinga et al ., ; Crapoulet et al ., ). Dune growth, however, may be interrupted by hydrodynamic processes, especially during stormy periods when elevated water levels and runup may reach and erode the dune (Sallenger, ).…”
Section: Introductionmentioning
confidence: 99%
“…Sand supply, surface moisture, vegetation characteristics, and wind velocity are, among others, characteristics that can drive spatial variations in coastal dune development, although just a few studies have been published on sand flat environments (Hesp 2002;van Heteren et al 2006;Poortinga et al 2015;Engelstad et al 2017;van Puijenbroek et al 2017). Zarnetske et al (2015) argue that, for a straight beach, vegetation and sand supply are important factors that control foredune morphology, depending on the time-scale considered and coastline position variability.…”
Section: Introductionmentioning
confidence: 99%
“…Zarnetske et al (2015) argue that, for a straight beach, vegetation and sand supply are important factors that control foredune morphology, depending on the time-scale considered and coastline position variability. Regarding sediment supply, some authors have suggested that water table depth and consequently surface moisture are important determinants for sediment supply and, consequently, for dune development (Hesp 2002;Bauer et al 2009;Poortinga et al 2015).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations